2006
DOI: 10.1021/bp050154o
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Doped Nanocomposites as Artificial-Cell-Based Biosensors: Detection of Listeriolysin O

Abstract: Listeriolysin O (LLO) is a pore-forming hemolysin secreted by the foodborne pathogen Listeria monocytogenes and is required for bacterial virulence. Current detection methods for L. monocytogenes are time-consuming, labor-intensive, and expensive, which is impractical considering the limitations of food storage. To overcome these problems, we developed a liposome-doped silica nanocomposite as a simple, inexpensive, and highly stable biosensor material that mimics existing whole-cell assays for LLO. Small unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…4 The sol-gel method has also been used to produce bioactive porous glasses for bone regeneration and to fabricate silica films on glass surfaces for cell-growth. 5,6 It has been observed that biological entities such as proteins and liposomes, 7,8 in addition to mammalian and prokaryotic cells, remain active on sol-gel derived surfaces after immobilisation or adhesion and can demonstrate increased stability and growth.…”
Section: Introductionmentioning
confidence: 99%
“…4 The sol-gel method has also been used to produce bioactive porous glasses for bone regeneration and to fabricate silica films on glass surfaces for cell-growth. 5,6 It has been observed that biological entities such as proteins and liposomes, 7,8 in addition to mammalian and prokaryotic cells, remain active on sol-gel derived surfaces after immobilisation or adhesion and can demonstrate increased stability and growth.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, single moleculebased biosensors may be more stable, but sometimes less functional compared to the whole cell counterpart (Zhao et al 2006). Synthetic materials are likely to be a feature of these two extremes, as extensively demonstrated by the latest bibliography on artificial biosensing systems, which mimic cells in their detection capabilities, showing also improved features in terms of robustness and sensitivity.…”
Section: Synthetic Cell-based Biosensorsmentioning
confidence: 99%
“…Moreover, conventional methods for identification of L. monocytogenes in food is a culture-based procedure that takes 5-7 days, consequently increasing the probabilities to commercialise a contaminated food product before the problem has been identified. For these reasons, the materials implemented by Zhao et al (2006) could be considered a good candidate to detect LLO, showing fast response (30 minutes) and high stability (at least 5 months in ambient conditions).…”
Section: Artificial Liposomesmentioning
confidence: 99%
“…In a study to detect Listeriolysin O (LLO), the liposomes were encapsulated in porous silica using alcohol-free sol-gel synthesis methods. The immobilized liposomes act as a cellular compartment containing the fluorescent dyes and the dye release due to the pore formation by LLO indicated the presence of the toxin (Zhao et al 2006).…”
Section: Toxinsmentioning
confidence: 99%